FAKTOR-FAKTOR YANG MEMPENGARUHI DIVIDEND POLICY PADA PERUSAHAAN MAKANAN, MINUMAN DAN TEMBAKAU YANG TERDAFTAR DI BURSA EFEK INDONESIA - YASODHARA INTAN PERMATANINGRUM; STEVEN YAP (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of this research is to test and analyze empirically the influence of Profitability, Liquidity, Tangibility, Growth Opportunity, Size, and leverage towards dividend policy. The object of this research is the food, beverage, and tobacco companies that listed in Indonesia Stock Exchange period 2004-2014. The purposive sampling is used as sampling technique, where 5 companies met the criteria and where analyzed using Eviews8 panel data regressions with fixed effect model to test the hypothesis. The result of this research shows that Profitability, Liquidity, Tangibility, and leverage influence dividend policy. Growth Opportunity, Size don’t affect the dividen policy.